Avaliação do potencial de contaminação por agrotóxicos em águas subterrâneas de abastecimento no Município de Russas – Ceará e as implicações na saúde humana - Mendes, Luzia Suerlange Araujo dos Santos (2023)
Water intended for human consumption must be free from contamination to avoid adverse health effects, whether through direct contact (ingesting the water, for example) or indirect contact (consuming vegetables, for example). Concern about water quality has led researchers to widely discuss the adverse effects that these substances can have on the environment and health. The indiscriminate use of pesticides is associated with environmental degradation and the emergence of malignant diseases such as lymphoma, leukemia, lung cancer, breast cancer, and endocrine and neurological problems, among others. The use of these substances causes chronic and acute intoxication characterized by effects such as breathing difficulties, vomiting, cramps, itching, diarrhea, convulsions, and even death. In this context, the research aimed to analyze the presence of pesticides in the canal water in the Tabuleiros de Russas Irrigation Project and in groundwater intended for human supply to discuss the implications for local health. The municipality of Russas has seen growth in agriculture due to the implementation of the Tabuleiros de Russas Irrigation Project; however, the increase in deaths from malignant neoplasms has occurred concomitantly with the rampant use of pesticides over the last 20 years. In this research, physical and chemical analyses of heavy metals in well water and canal water were carried out in 2019 and 2021, covering the dry and rainy seasons, respectively. Our pesticide analysis represents crops in four collection cycles: May, August, November 2021, and May 2022. The water analysis methods are described in the Standard Methods for the Examination of Water and Wastewater, using ICP-OES and liquid and gas chromatography. For potability, half of the samples were outside the limits established by Ordinance GM/MS No. 888/21 in both periods (dry and rainy). The metals aluminum, cadmium, total chromium, manganese, lead, and antimony did not comply with Ordinance No. 888/21. The pesticide analyses (μgL-1) in the first cycle detected Acephate+methamidophos (maximum of 11.71 and average of 4.32); Aldicarb+Aldicarb sulfoxide (maximum of 6.79 and average of 1.34); Dimethoate (maximum of 1.74 and average of 0.23); Imidacloprid (maximum of 1.89 and average of 0.41); Permethrin (maximum of 0.66 and average of 0.12) and Tebuconazole (maximum of 3.54 and average of 0.23). In the second cycle, Acephate+methamidophos (maximum of 572.0 and average of 77.94), Amethrin (maximum of 0.55 and average of 0.51), and Imidacloprid (maximum of 8.52 and average of 0.45). We did not detect substances in the third cycle. In the fourth cycle, the following substances were detected: Acephate+methamidophos (maximum of 150.50 and average of 35.16); Aldicarb+Aldicarb sulfoxide (maximum of 235.8 and average of 147.04); Imidacloprid (maximum of 8.52 and average of 0.53); carbofuran (maximum of 15.39 and average of 3.77); and Malation (maximum of 6.20 and average of 0.67). It was noted that all the samples are above the maximum values allowed by the European Union (EU), and the EU does not approve 88.9% of the substances detected and are related to malignant neoplasms. It is, therefore, essential that government entities intervene in the indiscriminate use of pesticides and promote programs to raise awareness of the use and control of these substances, such as the correct disposal of empty containers, which occurs inadequately due to a lack of information, environmental education, and inspection, and this can cause significant risks to the environment, compromising the potability of water and potentially causing serious harm to human health.